A low-complexity adaptive multisine waveform design for wireless power transfer - Clerckx,B; Bayguzina,E (IEEE Antennas and Wireless Propagation Letters, 2017)
Channel-adaptive waveforms for Wireless Power Transfer significantly boost the DC power level at the rectifier output. However the design of those waveforms is computationally complex and does not lend itself easily to practical implementation. We here propose a low-complexity channel adaptive waveform design whose performance is very close to that of the optimal design. Performance evaluations confirm the new design’s benefits in various rectifier topologies, with gains in DC output power of 100% over conventional waveforms.